2014
DOI: 10.7205/milmed-d-14-00151
|View full text |Cite
|
Sign up to set email alerts
|

Stellate Ganglion Block Used to Treat Symptoms Associated With Combat-Related Post-Traumatic Stress Disorder: A Case Series of 166 Patients

Abstract: Selective blockade of the right cervical sympathetic chain at the C6 level is a safe and minimally invasive procedure that may provide durable relief from anxiety symptoms associated with PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 40 publications
1
52
0
Order By: Relevance
“…The secondary literature search identified an additional 7 publications resulting in 32 publications included in the review. These comprised 15 case reports and case series, 1 systematic case review, 2 publications related to a single published RCT, and 14 nonsystematic reviews, opinions, guidelines, commentaries, books, and book chapters . The systematic search results are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The secondary literature search identified an additional 7 publications resulting in 32 publications included in the review. These comprised 15 case reports and case series, 1 systematic case review, 2 publications related to a single published RCT, and 14 nonsystematic reviews, opinions, guidelines, commentaries, books, and book chapters . The systematic search results are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Following publication of the review by Navaie and colleagues, the largest case series to date was published by Mulvaney et al., examining active‐duty military patients. This study reported patient follow‐up on a cohort of 166 patients for a period up to 6 months and found that administration of a second SGB could improve efficacy …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other paper was by Dr. Mulvaney (where the primary author of current report was the senior author) studies have shown that the SGB. improves blood circulation by inhibiting the activity of the sympathetic nervous system[3], it is not clear which circulation is being addressed and how long this vasodilation lasts. Actually, impact of SGB on circulation has been studied and has been demonstrated to have no impact[4].…”
Section: To the Editormentioning
confidence: 99%
“…For example, in chemically sympathectomized animals, antibody and cell-mediated responses are altered[5]. Central effect of SGB on NE, leading to its reduction, has been postulated by Dr. Mulvaney to explain significant effect of SGB on post traumatic stress disorder (PTSD), a condition known to have elevated NE levels[3]. Further evidence exists as to the SGB impact on proinflammatory cytokines.…”
Section: To the Editormentioning
confidence: 99%